Short Communication: Daily activities of Javan langurs (Trachypithecus auratus) in Gembira Loka Zoo, Yogyakarta, Indonesia - NATALIA FITRIYANI; LAURENTIA HENRIETA PERMITA SARI PURBA (Society for Indonesian Biodiversity, 2023)
Abstract. Fitriyani N, Purba LHPS. 2023. Short Communication: Daily activities of Javan langurs (Trachypithecus auratus) in Gembira Loka Zoo, Yogyakarta, Indonesia. Biodiversitas 24: 5278-5282. The Javan langur (Trachypithecus auratus) is one of the endemic primates of Java, Bali, and Lombok. The status of this species is vulnerable in their wild population; thus, the conservation effort is important to keep their existence. One of the conservation efforts is ex-situ conservation. Since this conservation is out of the animal's natural habitat, we must care about all aspects of animal welfare, including the physical and mental state, which can be observed from its behavior. This study aimed to analyze the daily activities of Javan langur living in an ex-situ conservation area named Gembira Loka Zoo. We observed and recorded the daily activity of seven individuals of Javan langur for about 250 hours, including holiday and non-holiday periods. This observation during holiday and non-holiday periods is intended to see whether there are differences in the behavior of Javan langur. The differences in number of visitors during the holiday period can reach thousands, whereas during the non-holiday period, there are only tens up to hundreds of loyal visitors per day. The result showed that the individuals spent most of their time on resting behavior (62.28% on holiday and 61.83% on non-holiday), followed by feeding (15.82% on holiday and 20.70% on non-holiday) and moving (12.01% on holiday and 12.64% on non-holiday). We analyzed the difference in their daily activities between holiday and non-holiday periods to observe the frequency of activity among those types of days. The Javan langurs showed a significant difference between those days only in social behavior (Mann-Whitney, p = 0.03). This study provides new behavioral data about the population of captive Javan langurs in Gembira Loka Zoo, which can be used as basic data for the conservation management of Javan langurs in captivity.